Does pregabalin offer potential as a first-line therapy for generalized anxiety disorder? A meta-analysis of efficacy, safety, and cost-effectiveness - Cardoner, Narcis; Gutiérrez-Rojas, Luis; Saiz, Pilar; Lahera, Guillermo; Álvarez-Mon, Miguel Ángel; Alonso Ortega, Pino; Pérez-Páramo, María (Frontiers in Pharmacology, 2025)
IntroductionGeneralized Anxiety Disorder (GAD) is a mental health condition with a recent increase in prevalence. GAD is often underdiagnosed, leading to negative consequences for individuals, healthcare systems, and society. The economic burden and impaired quality of life associated with GAD underscores the need for effective treatment. Pregabalin has shown promise in reducing anxiety symptoms; however, further research is needed to evaluate its efficacy and compare it with other treatment options. This study aimed to assess the efficacy, safety, and optimal pregabalin dosage for the treatment of GAD.MethodsThis meta-analysis followed PRISMA guidelines. Pregabalin-treated patients comprised the intervention group, whereas the comparator group received benzodiazepines, SSRIs, SNRIs, or placebo. Efficacy and safety were evaluated using various scales and adverse events (AEs). Randomized clinical trials were included in the study. Four major databases were used for this study. Outcome measures included the Hamilton Anxiety Rating Scale (HAM-A), Clinical Global Impression Improvement Scale (CGI-I), discontinuation rates, costs, and quality-adjusted life-years (QALYs). Meta-analyses were conducted using Review Manager 5.4 software, employing odds ratios (ORs) and mean differences (MDs) with 95% confidence intervals (CIs). Subgroup and sensitivity analyses were performed based on follow-up and dosage.ResultsFourteen studies involving 4,822 patients were analyzed. Pregabalin demonstrated superior efficacy in reducing HAM-A global scores at 2 weeks (MD −1.23, 95% CI −1.79 to −0.66), 4 weeks (MD −1.12, 95% CI −1.60 to −0.63), 8 weeks (MD −2.50, 95% CI −4.21 to −0.79), 12 weeks (MD 0.99, 95% CI 0.35–1.63), and 6 months to 1 year (MD −3.31, 95% CI −4.30 to −2.31). Pregabalin also showed a higher response rate to HAM-A (OR 1.51, 95% CI 1.31 1.75). CGI-I scores favored pregabalin (MD −0.25, 95% CI −0.38 to −0.12), with a higher response rate (OR 1.33, 95% CI 1.15–1.55). The discontinuation rates were lower with pregabalin (OR 0.80, 95% CI 0.70, 0.91). Adverse events favored pregabalin over SSRIs/SNRIs and benzodiazepines at different doses. Pregabalin was associated with higher cost-effectiveness (MD 0.02, 95% CI 0.01, 0.03).ConclusionPregabalin is an effective and well-tolerated treatment for generalized anxiety disorder, showing superior efficacy and safety compared with first-line medications.Systematic Review RegistrationPROSPERO CRD42024556152.